The Effect of Elderly Gymnastics on Menopausal Women on Decreased Body Fat - Sri Mulyati; Novita Rina Antarsih; Karningsih; Dewi Nirmalasari (International Journal of Science and Society, 2021)
Decreased body fat is an important thing to do in menopausal women whose estrogen levels decrease with the addition of age. One way to lose body fat is elderly gymnastics. The elderly gymnastics movement has evolved a lot but no senior gymnastics has focused on body fat loss. The aim of this study is to find out the effect of elderly gymnastics modification on the decrease in body fat in menopausal women. Method of this research is quasi-experimental, in 35 menopausal women given modified elderly gymnastics focused on the reduction of body fat, while 35 respondents with standard senior gymnastics. This study with a frequency of 1x/week for 3 months. After doing senior gymnastics modification 12 times for 3 months, there was an average difference in the percentage of total body fat menopause in all four measurements between groups of 5.5%, elderly gymnastics modification as well as elderly gymnastics older version maintains the stability of visceral fat percentage in menopausal women, a decrease in abdominal fat thickness of 1.1 mm with an average difference between the 3rd and 4th measurements by 7.6%. Abdominal circumference in menopausal women decreased in the treatment group by 1 cm, while in the control group experienced an increase of 0.3 cm after 3 months of treatment. In the treatment group, there was a decrease in triglyceride levels after treatment compared to the control group. Elderly gymnastic modification can decrease body fat gradually after the 2nd month (8th week) intervention in menopausal women.